Legal Clinical Education: Ukrainian Experience - Saienko, Maryna I. (2020)
The relevance of the article is stipulated by the necessity to study a specific type of legal education – legal clinical education. However, legal clinics are the basis for the practical training and students' practice implementation i.e. they allow to transfer the obtained theoretical knowledge into the practical ones. The purpose of the study is to analyze the peculiarities of formation and development of the abovementioned education in Ukraine in general, and in imitation of the Legal Clinic “Istyna” of Dnipropetrovsk State University of Internal Affairs activities, in particular, as well as to determine the prospects of the legal clinical movement. The basic methods in the study of this issues are the following: the historical method; the method of analysis. The method of prediction to determine the prospects for the further development of legal clinical education in Ukraine in the context of integration into the European educational area and the Concept of Legal Education Development was also applied. The article elucidates the concept “legal clinical education”, focuses on the necessity for this type of education, and determines the prospects of achieving quality results of legal clinical education, taking into account its components in the domestic legal education by the imitation of the legal clinic “Istyna” of Dnipropetrovsk State University of Internal Affairs. The materials of the article may be useful in future studies of the legal clinics activities and functioning and implementation of the concept legal of education development in Ukraine.